Committing the Offense of Intentional Injury with “Any Instrument, Not Having Been Specifically Manufactured for the Purpose of Attack or Defense, Which May Be Used for Such Purpose” and is Accepted as a Weapon - Eylem Baş (Ceza Hukuku ve Kriminoloji Dergisi)
The commission of the offense of intentional injury with a weapon is included as a secondary element requiring the aggravation of the penalty in subparagraph (e) of paragraph 3 of Article 86 of the Turkish Penal Code numbered 5237 (TCK). According to the 4th subparagraph of paragraph (f) of Article 6 of the TCK, “in the implementation of the criminal law,” it is stated that “[a]ny instrument, not having been specifically manufactured for the purpose of attack or [defense], which may be used for such purpose” will be understood as a weapon. However, it is not clear what should be understood from the aforementioned expression in subparagraph 4. In this study, the problems caused by the phrase “[a]ny instrument, not having been specifically manufactured for the purpose of attack or defense, which may be used for such purpose” will be examined in practice. Subsequently, the necessity of abolishing the 4th subparagraph and using another expression with an amendment to be made in article 6 or the subparagraph (e) of the 3rd paragraph of article 86 of the TCK will be emphasized.